The Inventory of Anal Sex Knowledge (iASK): A New Measure of Sexual Health Knowledge Among Adolescent Sexual Minority Males. Issue 3 (25th January 2022) - Kutner, Bryan A.; Perry, Nicholas S.; Stout, Claire; Norcini Pala, Andrea; Paredes, Christian D.; Nelson, Kimberly M.
ABSTRACT: Introduction: Knowledge about sexual health is a key determinant of sexual behavior among adolescent sexual minority males (ASMM). No measures exist to assess anal sex knowledge, even though anal sex is the primary route by which ASMM acquire sexually transmitted infections (STIs), including a disproportionate burden of human immunodeficiency virus (HIV). Aim: We developed a new measure as a first step toward assessing the prevalence and correlates of anal sex knowledge and potential effects of interventions to improve knowledge. Methods: Two coders independently outlined domains of knowledge within 2 sex education videos designed to address anal sex knowledge among ASMM. An initial set of 56 items, some duplicative, encompassed all domains. A larger team, including a psychometrician, then iteratively revised and reduced the set of items, and assessed construct validity via cognitive testing among ASMM (N = 4, aged 16–17 years old, 75% identifying as racial/ethnic minorities). For the final set of 10 items, factor structure and convergent and divergent validity were assessed using baseline responses to an online survey within a randomized controlled pilot trial among 154 ASMM. Open-ended questions assessed their comprehension and the acceptability of items. Outcomes: We examined correlates that we anticipated would be theoretically related (ie, the HIV Knowledge Questionnaire [HIV-KQ-18] and the STD-Knowledge Questionnaire [STD-KQ]) and theoretically distinct (ie, the Patient Health Questionnaire [PHQ-2], Generalized Anxiety Disorder scale [GAD-2], and employment status). Results: The one-factor model explained 42% of the items' common variance and demonstrated acceptable internal reliability (Cronbach's alpha = 0.72). The measure withstood tests of convergent and divergent validity when compared to current measures (HIV knowledge, r = 0.35 and STI knowledge, r = 0.24, both P < .05; internalizing mental health symptoms, r = -0.07 and employment status, r = 0.13, both P > .05). Few respondents found words unfamiliar or uncomfortable. Clinical Implications: A method for assessing anal sex knowledge may offer opportunities to intervene to lessen harmful sequelae of a lack of knowledge. Strength & Limitations: We developed a brief, psychometrically valid measure of anal sex knowledge. The measure may neither generalize to all anal health knowledge nor to more sexually experienced, older SMM. Conclusion: The resulting 10-item, single-factor measure, the Inventory of Anal Sex Knowledge (iASK), is psychometrically sound and addresses the lack of anal sex knowledge measures among ASMM. The iASK can function to assess the prevalence and sequelae of anal sex knowledge among ASMM as well as the impact of interventions targeting anal sex knowledge.